2017
DOI: 10.1016/j.lrp.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Ready to be Open? Explaining the Firm Level Barriers to Benefiting From Openness to External Knowledge

Abstract: This paper provides new theory and evidence about the benefits of openness on a firm's innovation performance and, more importantly, the specific firm-level contingencies under which those benefits are more (or less) likely to be observed. Building on Dyer and Singh's (1998) relational view, we suggest that a firm's lack of resources and absorptive capacity, as well as its use of secrecy, are significant barriers to benefiting from openness to external knowledge. Using responses from 12,152 firms to the fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 102 publications
3
124
0
5
Order By: Relevance
“…Sieg, Wallin, and Von Krogh 2010;Lüttgens et al 2014). Furthermore, there has been a limited focus on failures, costs and downsides of OI (Faems et al 2010;Laursen and Salter 2014;Monteiro, Mol, and Birkinshaw 2016). In general, future research needs to add to a better understanding of how firms can profit from OI by aligning OI strategies to the business model (Baden-Fuller and Haefliger 2013) and governing inter-organisational relationships (Hagedoorn and Zobel 2015).…”
Section: Appendixmentioning
confidence: 99%
“…Sieg, Wallin, and Von Krogh 2010;Lüttgens et al 2014). Furthermore, there has been a limited focus on failures, costs and downsides of OI (Faems et al 2010;Laursen and Salter 2014;Monteiro, Mol, and Birkinshaw 2016). In general, future research needs to add to a better understanding of how firms can profit from OI by aligning OI strategies to the business model (Baden-Fuller and Haefliger 2013) and governing inter-organisational relationships (Hagedoorn and Zobel 2015).…”
Section: Appendixmentioning
confidence: 99%
“…Trust is the expectation that one partner will not exploit the vulnerabilities of the other when there is an opportunity to do so (Krishnan, Martin, and Noorderhaven, 2006). It is critical to inter-firm partnerships in general (Ring and Van de Ven, 1994) and external knowledge sourcing in particular (Monteiro, Mol, and Birkinshaw, 2015). Scouts understood that by developing close relationships with BU managers, those managers gradually opened up to them.…”
Section: Pierre Offered a Complementary Perspectivementioning
confidence: 99%
“…According to the arguments developed so far, it may be concluded that international inbound open innovation provides numerous advantages. Nevertheless, some studies, according to an alliance portfolio perspective, acknowledge that it may pose certain threats and that its proper management requires constant attention (Love et al, 2014;Monteiro et al, 2016;Wassmer, 2010). Several works have found empirical evidence that shows a negative relationship between an extensive network of international partners and firm performance (D'Ambrosio et al, 2016;Goerzen & Beamish, 2005;Lavie & Miller, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Externalizing innovation lets firms integrate and develop new knowledge from international sources and obtain strategic innovations through an open innovation approach (Chesbrough & Crowther, 2006). This approach can shed light on circumstances in which innovation externalization leads to better international performance (Monteiro, Mol, & Birkinshaw, 2016).…”
Section: Introductionmentioning
confidence: 99%